Mapping perceptions of species' threats and population trends to inform conservation efforts: the Bornean orangutan case study - Abram, N.K.; Meijaard, E.; Wells, J.A.; Ancrenaz, M.; Pellier, A.S.; Runting, R.K.; Gaveau, D.L.A.; Wich, S.; Nardiyono; Tjiu, A.; Nurcahyo, A.; Mengersen, K. (Wiley, 2015)
We demonstrate a robust approach for predicting and mapping threats and population trends of wildlife species, invaluable for understanding where to target conservation resources. We used the endangered Bornean orangutan (Pongo pygmaeus) as our case study to facilitate and strengthen conservation efforts by the Indonesian government to stabilize populations by 2017.Kalimantan, Indonesian Borneo.Local knowledge of threats to orangutan populations was gathered through questionnaire interviews in 531 villages (512 in Kalimantan) within known orangutan range. These data were integrated with 39 environmental/socio‐economic spatial variables using boosted regression tree modelling to predict threat levels and population trends across Kalimantan and to identify key combinations of threats and trends that can help to direct appropriate conservation actions.Nineteen percentage of villages surveyed in Kalimantan reported human–orangutan conflicts. High‐predicted conflict likelihood was extensive, strongly associated with road density (very low or high) and temperature seasonality. Recent orangutan killings were reported in 23% of villages. High killing risk was highly associated with greater surrounding orangutan habitat and for villages more than 60 km from oil palm plantations. Killings by respondents were reported in 20% of villages with higher likelihoods associated with greater range in rainfall and temperature, and higher proportion of Christian believers. Orangutan populations were predicted to decline/become locally extinct across the majority of their range in Kalimantan over the next decade, with few regions predicted to support stable populations.Human–orangutan conflicts and killings occur extensively in Kalimantan, with many populations at risk of decline or localized extinctions. Effective conservation actions are therefore urgently needed. Our approach better informs conservation managers in understanding the extent, spatial patterns and drivers of threats to endangered species such as the orangutan. This is essential to better design management strategies that can minimize or avert the species' decline.